2021
DOI: 10.3390/children8090726
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Pulmonary Vein Stenosis Due to Total Anomalous Pulmonary Venous Connection Repair in Children: Extravascular MDCT Findings

Abstract: Purpose: To evaluate extravascular findings on thoracic MDCT angiography in secondary pulmonary vein stenosis (PVS) due to total anomalous pulmonary venous connection (TAPVC) repair in children. Materials and Methods: All patients aged ≤18 years with a known diagnosis of secondary PVS after TAPVC repair, confirmed by echocardiography, conventional angiography, and/or surgery, who underwent thoracic MDCT angiography studies between July 2008 and April 2021 were included. Two pediatric radiologists independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 20 publications
(54 reference statements)
2
4
0
Order By: Relevance
“…The findings of our study correlate well with the findings from previously published studies in pediatric patients with primary and secondary PVS focusing on extrathoracic MDCT findings [16][17][18]. These studies also identified the presence of three main extravascular pleuropulmonary abnormalities on thoracic MDCT in pediatric patients with PVS: GGO, septal thickening, and pleural thickening.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The findings of our study correlate well with the findings from previously published studies in pediatric patients with primary and secondary PVS focusing on extrathoracic MDCT findings [16][17][18]. These studies also identified the presence of three main extravascular pleuropulmonary abnormalities on thoracic MDCT in pediatric patients with PVS: GGO, septal thickening, and pleural thickening.…”
Section: Discussionsupporting
confidence: 90%
“…Presented clinical signs and symptoms in these 49 pediatric patients included: failure to thrive (n = 8; 16.3%), pulmonary hypertension (n = 7; 14.3%), shortness of breath (n = 5; 10.2%), hypoxemia (n = 5; 10.2%), fever (n = 3; 6.1%), and bradycardia (n = 2; 4.1%). Extrapulmonary MDCT findings for a subset of these patients were previously reported [16][17][18].…”
Section: Patient Population Characterizationmentioning
confidence: 74%
See 3 more Smart Citations